2021
DOI: 10.1002/ski2.27
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparity in skin carcinogenesis and potential influence of sex hormones

Abstract: Background: Sex or gender disparity in skin cancer has been documented for a long time at the population level. UV radiation (UVR) is a common environmental risk for all three major types of skin cancer: cutaneous melanoma (CM), basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC). The underlying mechanism for sex disparity has been largely attributed to sex-differentiated behaviour patterns related to UVR. Non-UVR factors such as intrinsic physiological differences have been suggested but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 114 publications
(248 reference statements)
0
8
0
Order By: Relevance
“…The increased incidence is often attributed life-style choices. However, more recent research suggests an underlying biological cause [ 139 , 142 ]. Some scarce evidence infers a role of hormonal signalling in modulating EMT in cSCC.…”
Section: Resultsmentioning
confidence: 99%
“…The increased incidence is often attributed life-style choices. However, more recent research suggests an underlying biological cause [ 139 , 142 ]. Some scarce evidence infers a role of hormonal signalling in modulating EMT in cSCC.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review revealed an increasing suspicion regarding the role of sex hormones in melanoma risk, but concluded there is currenty insufficient epidemiological or molecular evidence at this point. 14 The limitations of this case study include small pedigree size and lack of clinical phenotypic data from the brother. Functional evaluation of the PARP1 variant and the potential interactions with TYR were beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 97%
“…As both AHM‐affected individuals are females, we considered the possible role of sex hormones. A recent review revealed an increasing suspicion regarding the role of sex hormones in melanoma risk, but concluded there is currenty insufficient epidemiological or molecular evidence at this point 14 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on Caucasian populations have demonstrated an association between cutaneous melanoma and basal cell melanoma and UV index in young women but not in menopausal women; thus, female hormones' regulatory effects on mutagenesis may be a valid hypothesis. On the contrary, the risk for this event in men gradually increases with age [133]. A potential explanation may be provided by further studies examining sex hormones' role in melanoma progression.…”
Section: Atherosclerosismentioning
confidence: 99%